EQUATION OF STATE OF IRON-SILICON ALLOYS TO MEGABAR PRESSURE - Hirao N.; Ohtani E.; Kondo T.; Kikegawa T. (My University, 2004)
The stability and pressure–volume equation of state of iron–silicon alloys, Fe-8.7 wt% Si and Fe-17.8 wt% Si, have been investigated using diamond-anvil cell techniques up to 196 and 124 GPa, respectively. Angular–dispersive X-ray diffractions of iron–silicon alloys were measured at room temperature using monochromatic synchrotron radiation and an imaging plate (IP). A bcc–Fe-8.7 wt% Si transformed to hcp structure at around 16∼36 GPa. The high-pressure phase of Fe-8.7 wt% Si with hexagonal close-packed (hcp) structure was found to be stable up to 196 GPa and no phase transition of bcc–Fe-17.8 wt% Si was observed up to 124 GPa. The pressure–volume data were fitted to a third-order Birch–Murnaghan equation of state (BM EOS) with zero–pressure parameters: V 0=22.2(8) Å3, K 0=198(9) GPa, and K‘0=4.7(3) for hcp–Fe-8.7 wt% Si and V 0=179.41(45) Å3, K 0=207(15) GPa and K‘0=5.1(6) for Fe-17.8 wt% Si. The density and bulk sound velocity of hcp–Fe-8.7 wt% Si indicate that the inner core could contain 3–5 wt% Si.
Keywords: Iron–silicon alloys; High pressure; X-ray diffraction; Equation of state